REPRESENTASI IDENTITAS BUDAYA DAN ARKEOLOGI: KAJIAN FASAD BANGUNAN RUMAH SAKIT DI KAWASAN KOTABARU, YOGYAKARTA (TAHUN 1901–1929) - Larasati, Retno; Assilmi, Ghilman (Multikultura, 2025)
Identity is dynamic and influenced by various factors, one of which is culture. This research is an archaeological study that reviews how identity can be represented through material culture. One form of material culture is the facade of a hospital building in Kotabaru area, Yogyakarta from 1901-1929. Hospital buildings as colonial heritage material culture can be an example of how culture can be represented in physical or material form. This research uses four hospitals as primary data, including Bethesda Hospital, dr. Soetarto Hospital, Dr. Yap Eye Hospital and Panti Rapih Hospital. This research uses the archaeological method which consists of three stages, namely data collection, processing, and interpretation. The purpose of this research is to describe the facades of hospital buildings in Kotabaru area, Yogyakarta and explain the building facades that represent the cultural identity of the group they represent. This research proves that the cultural identity of the group and individual founders of hospital buildings is reflected through the facades. The different facade styles of the four buildings are also an accumulation of external factors, namely the socio-politics of the Dutch colonial government and the Yogyakarta Sultanate.